The Level of Millennial Farmers' Understanding of The Use of Garden Land In Sidenreng Rappang District - Saade, Aminuddin; Syamsuddin, Syamsuddin; R, Fitriani; Apriani, Wulansari (EQUATOR SINAR AKADEMIA, 2024)
An alternative to overcoming the food crisis is to use yardland more productively. More productive use of yard land can be done by productive human resources who have a good and high level of understanding. This research was conducted in Bina Baru village, Kulo District, Sidenreng Rappang Regency, South Sulawesi. The aim is to increase millennial farmers' understanding of food availability through the use of yard land. The method used is descriptive-qualitative through a quantitative approach with a questionnaire instrument for millennial farmers aged 19 - 39 years and domiciled in the above villages. The sampling technique is purposive sampling. The results of this research are that 66% (9110 people) of the 13939 residents of Kulo District are of productive age. The yard area of this sub-district is 201.22 ha, of which 55 ha has been used for vegetable commodities. Millennial farmers' understanding of the use of yard land is high to very high. The value of the relationship between factors (paired correlation) is from weak (0.10) to moderate and significant (0.53). The value of the relationship together (multiple correlation) is the respondent's response to each question/statement with the total score as the Y factor; namely, the factors that are influenced are from a moderate correlation value (0.54) and significant to a weak correlation which is not significant (0.05). The quality of respondents' understanding of the use of yard land is good (60 points). The understanding score of all respondents (50 people) on the 15 questions was good, with an average score of 60. Respondents' understanding was good, with a high score and percentage category.